2023
DOI: 10.3390/rs15082078
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Fast Convergence Gray-Level Co-Occurrence Matrix for Sea Surface Wind Direction Extraction from Marine Radar Images

Abstract: The new sea surface wind direction from the X-band marine radar image is proposed in this study using a fast convergent gray-level co-occurrence matrix (FC-GLCM) algorithm. First, the radar image is sampled directly without the need for interpolation due to the algorithm’s application of the GLCM to the polar co-ordinate system, which reduces the inaccuracy caused by image transformation. An additional process is then to merge the fast convergence method with the optimized GLCM so that the circular transition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The research findings supported the effectiveness of the proposed approach in detecting contrast enhancement when forensic fingerprints are tampered with anti-forensic attacks, achieving a true positive rate (TPR) of 92.0%. Another study [34] utilized an approach that combined the rectangularto-polar coordinate transformation, previously introduced by [35], with GLCM. The proposed model in their study demonstrated improved accuracy and computational speed compared to the classical GLCM method.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The research findings supported the effectiveness of the proposed approach in detecting contrast enhancement when forensic fingerprints are tampered with anti-forensic attacks, achieving a true positive rate (TPR) of 92.0%. Another study [34] utilized an approach that combined the rectangularto-polar coordinate transformation, previously introduced by [35], with GLCM. The proposed model in their study demonstrated improved accuracy and computational speed compared to the classical GLCM method.…”
Section: Related Workmentioning
confidence: 99%
“…Referring to [32] and the successful research [34], the combination of polar transformation and GLCM feature extraction shows promising potential when applied to circular-shaped objects. This is because the integration of polar transformation with GLCM allows for the modeling of texture that not only considers the spatial relationships between neighboring pixels in the image but also considers the radial representation of the texture.…”
Section: Related Workmentioning
confidence: 99%